Review Of Inactive Medical Record Destruction Activities At Hermina Hospital Palembang Year 2021 - Terra Amalia; Ria Angraini (Green Publisher Indonesia, 2021)
Various methods and systems used to improve the quality of the management and storage of medical record files, one of which is to reduce the volume of archives that have no use value, to reduce archive buildup and create better and more efficient storage space, making it easier for officers to carry out their duties search and expedite the patient's treatment process. This study uses a qualitative type of research, with a descriptive method. The data collection in this study used the interview and observation (checklist) method. The population in this study were officers of the medical record work unit at Hermina Hospital Palembang in 2021. Based on the research, it can be concluded that the retention of inactive medical record files in 2021 is being carried out by medical record officers and the destruction of inactive medical record files has not been carried out because constrained by the COVID-19 pandemic, there are officers who carry out WFH (Work from Home) along with service hours. At the Hermina Hospital in Palembang, the standard operating procedure (SOP) regarding the destruction of inactive medical record files at the Hermina Palembang hospital already exists, but has not been implemented is 0.000 <0.05, it can be concluded that it is accepted, meaning that there is a difference in scores between before and after being treated with water tube media